Computer organization and architecture designing for performance - Stalling, William (Pearson Eduacation, 2010)
Four-time winner of the best Computer Science and Engineering textbook of the year award from the Textbook and Academic Authors Association, Computer Organization and Architecture: Designing for Performance provides a thorough discussion of the fundamentals of computer organization and architecture, covering not just processor design, but memory, I/O, and parallel systems. Coverage is supported by a wealth of concrete examples emphasizing modern RISC, CISC, and superscalar systems. Undergraduates and professionals in computer science, computer engineering, and electrical engineering courses will learn the fundamentals of processor and computer design from this award-winning text. The eighth revision has been updated to reflect major advances in computer technology, including multicore processors and embedded processors. Interactive simulations have been expanded and keyed into relevant sections of text.